Growing up with risk - Thom, Betsy ca. 20./21. Jh; Sales, Rosemary 1947-; Pearce, Jenny 1956- (Policy, 2007)
This book provides a critical analysis of ways in which risk assessment and management are defined and applied in policy, theory and practice in relation to children and young people. It explores the complexities of balancing responsibility for protecting the young with the benefits of risk-taking and the need to allow experimentation